Electric spark alloying with ZrN-based electrode material - Paustovsky, A.V.; Novikova, V.I.; Mordovets, N.M. (Functional Materials, 2006)
Dependences of erosion characteristics have been studied for ZrN-(Cr, Ni, Аl₂O₃) electrode material and relations have been established between the phase composition, structure, and tribotechnical properties of coatings formed bу electric spark alloуing techniques.